(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2015)
In this case we report a 27 year old primigravida having 14 weeks of pregnancy with torsion of ovarian cyst. She presented to a private clinic with acute pain in right lower abdomen. She was diagnosed to have torsion of ovarian cyst during pregnancy and laparoscopic cystectomy was done. Histopathology report showed benign serous cystadenoma. Her pregnancy was followed up. She delivered a healthy baby at term. Though the safety of antepartum surgical intervention has been accepted, laparoscopic surgery needs more advanced surgical skill and knowledge. J. Paediatr. Surg. Bangladesh 4(2): 67-71, 2013 (July)